2017
DOI: 10.2174/1568009616666161229145115
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin D as a Promising Target for the Discovery of Novel Anticancer Agents

Abstract: In this review, PubMed, Sci-finder and other search engines were used to gather information on Cathepsin D. The necessary and relevant information was thoroughly studied to make the article appropriate to highlight all the aspects related to Cathepsin D and its role in cancer. Findings & Conclusion: The present review illustrates structural, functional and regulatory aspects of CATD in cancer, its significant role in angiogenesis, metastasis, invasion, apoptosis, cell proliferation, and therapeutic potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Taken together, cathepsins D and K, both extensively studied for their potential as therapeutic targets in e.g. cancer, Alzheimer or Parkinson disease 53 , 54 , may have potential as targets for novel DN treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, cathepsins D and K, both extensively studied for their potential as therapeutic targets in e.g. cancer, Alzheimer or Parkinson disease 53 , 54 , may have potential as targets for novel DN treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of CTSs has been widely explored over the last decades in the field of chronic inflammatory diseases [27,37,204,205], cardiovascular diseases [10,19,181], osteoporosis [70][71][72][73], arthritis [28,206], kidney diseases [30][31][32]84], pancreatitis [207], obesity [208][209][210], cancer [25,34,48,74,82,211], neurodegenerative diseases [39,41,184,185,212,213], and many other pathological states. Multiple inhibitors are currently available, ranging from reversible covalent inhibitors to irreversible inhibitors [214][215][216][217][218] (Table 4).…”
Section: Cathepsin Inhibitors and Their Therapeutic Applicationsmentioning
confidence: 99%
“…In the case of breast cancer, Derocq et al demonstrated that CATD secreted in the extracellular environment triggers fibroblast outgrowth by binding to the β-chain of the LDL receptor-related protein-1 (LRP1), a scavenger receptor mediating the endocytosis of various extracellular ligands and involved in signal transduction and gene transcription (88). The multiple roles of CATD show increasing promise for the development of novel anticancer agents (89).…”
Section: Cathepsin D and Transglutaminase 2 (Tgm2)mentioning
confidence: 99%